2022
DOI: 10.1186/s12903-022-02401-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-transcriptome analysis of periodontal tissue and construction of immune-related competitive endogenous RNA network

Abstract: Background In periodontitis, noncoding RNAs may play a regulatory role in the immune microenvironment through competitive endogenous RNA. We aimed to profile noncoding RNA expression and construct immune-related ceRNA network in periodontitis. Methods Five inflamed periodontal tissue and five healthy gingivae were collected for whole-transcriptome sequencing. Differential gene, functional enrichment, and protein–protein interaction network analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The results show neutrophil chemotaxis, chemokine activity, and CXCR binding were elevated in inflammatory gingival tissues according to the enrichment analysis of the C5 GO genomic dataset. 18 In addition, we identified 10 hub genes from the protein-protein interaction network using topological analysis. And most of the hub genes were associated with chemokines and chemokine receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show neutrophil chemotaxis, chemokine activity, and CXCR binding were elevated in inflammatory gingival tissues according to the enrichment analysis of the C5 GO genomic dataset. 18 In addition, we identified 10 hub genes from the protein-protein interaction network using topological analysis. And most of the hub genes were associated with chemokines and chemokine receptors.…”
Section: Introductionmentioning
confidence: 99%
“…We found that CXCR1 and PPBP were also included. 18 As CXCR1 and PPBP are important members of chemotaxis-related molecules, and play an important role in the induction and activation of neutrophils together with IL-8, it is of interest how their expression in gingival tissues.…”
Section: Introductionmentioning
confidence: 99%